STRUCTURAL GEOLOGY ANALYSIS AND GEOMECHANICAL IMPLICATION FOR NATURALLY FRACTURED BASEMENT RESERVOIR PREDICTION IN L AREA, SOUTH SUMATRA BASIN, INDONESIA - DARMAWAN, WINDI
Fractured basement reservoir has been a new exploration objective in the South Sumatra Basin, Indonesia. Hydrocarbon indication from exploration wells and significant hydrocarbon production from fractured basement reservoir in South Sumatra Basin has proved the occurrence of hydrocarbon and potential to be explored as a new exploration play. Structural geology approach and good understanding of fractured characterization has been proved as an effective method to identify high intensity fractured basement area which applied in L area for naturally fractured basement reservoir exploration. L area is located in the South Sumatra Basin, a prolific Tertiary basin in the western of Indonesia. Seismic structural interpretation combined with Palinspatic restoration has observed the two deformation styles in this area. Regional tectonics evolution in South Sumatra Basin was initiated by extensional system in the Eocene - Oligocene then a continues period of contractional tectonics, involving strike-slip and thrust system, dominated in the Upper Miocene to Pliocene time and reactivated the older structures in this area. Complex tectonics system of South Sumatra Basin has resulted most of structural traps and also indicated the potential fractured reservoir in the hard rock basement that consists of igneous rocks and low-grade methamorphic rocks. The main purpose of this fractured basement reservoir study is to build an appropriate naturally fractured basement reservoir model with structural geology approach using seismic data, geomechanics data, and rock mechanical properties. Faults analysis shown that normal and reverse faults were not potential to be reactivated by in situ present day stress and could hold maximum pore pressure 31 Mpa. Natural fractured prediction indicates potential fracture oriented to the NW-SE, normal type with dip 730 and reverse type with low angle dip 170 which distribute along the NW-SE and NE-SW faults. Low intensity fractured and potentially sealed in L area were indicated by low Slip tendency value 0,2. Integrated structural geology analysis, geomechanics, and consistent fractured model with tectonics and structural geology concept is the best way to evaluate and predict naturally fractured basement reservoir, particularly when dealing with limited subsurface data in exploration.